The role of mTOR during cisplatin treatment in an in vitro and ex vivo model of cervical cancer. (1st September 2015) - Leisching, G.R.; Loos, B.; Botha, M.H.; Engelbrecht, A.-M.
Highlights: A low, non-cytotoxic concentration of cisplatin is utilised. We elucidate the role of mTOR in response to cisplatin and combination treatments Cytotoxicity of cisplatin is greatly enhanced when mTOR is inhibited. Abstract: Cisplatin is used as a cytotoxic agent for the management of cervical cancer. However, the severity of the side-effects limits the use of this drug, particularly at high doses. Resistance to cisplatin is often attributed to a disruption in the normal apoptotic response via aberrant activation of pathways such as the mTOR pathway. Here we assess the role of mTOR and its effect on cell death sensitization and autophagy in response to a low concentration of cisplatin in cervical cancer cells. Additionally we measured the expression profile of mTOR in normal, low- and high-grade squamous intraepithelial (LSIL and HSIL) lesions and cancerous tissue. An in vitro model of cervical cancer was established using HeLa and CaSki cells. mTOR protein expression as well as autophagy-related proteins were evaluated through Western blotting. Inhibition of mTOR was achieved with the use of rapamycin and RNA silencing. A low concentration of cisplatin administered as a single agent induces autophagy, but not apoptosis. Cisplatin cytotoxicity was greatly enhanced in cancer cells when mTOR had been inhibited prior to cisplatin treatment which was likely due to autophagy being increased above cisplatin-induced levels, thereby inducing apoptosis. Cervical tissue samples revealed an increase in mTOR protein expression in LSIL and carcinoma tissue which suggests a change in autophagy control. Our data suggest that utilising a lower dose of cisplatin combined with mTOR inhibition is a viable treatment option and addresses the challenge of cisplatin dose-dependent toxicity, however future studies are required to confirm this in a clinical setting.